Herbicides selectivity in pre-budded seedlings of sugarcane - Dias, José Luiz Carvalho De Souza; Silva Junior, Antonio Carlos Da; Queiroz, Juliana Roberta Gobi; Martins, Dagoberto (Instituto Biológico, 2017)
ABSTRACT: Herbicides are expected to show selectivity towards cultivated plants, i.e., they ought to control weeds without jeopardizing the development and productivity of crops. The objective of this project was to evaluate the selectivity of herbicides applied in pre-planting of three sugar cane cultivars which were planted according to the system of pre-budded seedlings (PBS) under climatic natural conditions, between September and November of 2013. The experiment was set according to a completely random design with four replications. The treatments were distributed according to a factorial scheme of 3 × 8, in which factor A was the cultivar (CTC14, CTC7, and RB966928), and factor B was the herbicide (in g.ha-1): S-metolachlor (2,640), clomazone (1,000), sulfentrazone (800), diclosulam (200), metribuzin (1,920), diuron + hexazione (1,170 + 330), S-metolachlor + sulfentrazone (2,640 + 800), and a no treatment. The visual symptoms of intoxication were evaluated 14, 28, 35, 42, 49, 56, and 63 days after application (DAA), the height and number of tillers 14, 35, 49, 56, and 63 DAA, the dry weight of shoot (DWS), and the dry weight of root (DWR) 63 DAA. Under the conditions of the experiment, the herbicides S-metolachlor, clomazone, metribuzin, diuron + hexazinone, and S-metolachlor + sulfentrazone were selective towards the presprouted sugar-cane plantlets. Diclosulam was the less selective herbicide, followed by sulfentrazone. Cultivar CTC14 was visually the less tolerant to the herbicides diclosulam and sulfentrazone.

RESUMO: Os herbicidas devem apresentar seletividade às culturas agrícolas, ou seja, controlar as plantas daninhas sem comprometer o desenvolvimento nem a produtividade da cultura. O objetivo deste trabalho foi avaliar a seletividade de herbicidas aplicados em pré-plantio de três cultivares de cana-de-açúcar plantados pelo sistema de mudas pré-brotadas (MPB). O experimento foi desenvolvido na Usina São Martinho, próximo ao município de Pradópolis (SP), sob condições naturais de clima, no período de setembro a novembro de 2013. O delineamento experimental utilizado foi o inteiramente casualizado, com quatro repetições. Os tratamentos foram distribuídos em esquema fatorial (3 × 8), sendo o fator A composto de três cultivares: CTC14, CTC7 e RB966928; e o fator B por sete herbicidas (em g.ha-1): S-metolachlor (2,640); clomazone (1,000); sulfentrazone (800); diclosulam (200); metribuzin (1,920); diuron + hexazinone (1,170 + 330); S-metolachlor + sulfentrazone (2,640 + 800); mais uma testemunha sem aplicação de herbicidas. Foram avaliados os sintomas visuais de fitointoxicação aos 14, 28, 35, 42, 49, 56 e 63 dias após aplicação (DAA), a altura e o número de perfilhos dos cultivares aos 14, 35, 49 e 63 DAA, a massa seca da parte aérea (DWS) e a massa seca do sistema radicular (MSSR) aos 63 DAA. Nas condições em que o experimento foi conduzido, os herbicidas S-metolachlor, clomazone, metribuzin, diuron + hexazinone e S-metolachlor + sulfentrazone foram seletivos às mudas pré-brotadas de cana-de-açúcar. O herbicida diclosulam foi o menos seletivo, seguido do sulfentrazone. O cultivar CTC14 apresentou-se visualmente menos tolerante aos herbicidas diclosulam e sulfentrazone.
Seletividade de herbicidas em mudas pré-brotadas de cana-de-açúcar
Keywords: chemical control; phytointoxication; Saccharum spp.; pre-planting; controle químico; fitointoxicação; Saccharum spp.; pré-plantio